(untitled) (Signos do Consumo, 2017)
This article aims to present the concept of corporate culture, as well as to demonstrate its essentiality in branding strategies. As it is a determining factor of the success of branding, corporate culture can favor strategic paths, but it can also make them unfeasible, necessitating, therefore, interventions and adjustments for their feasibility. The methodology proposed here is the “3Es”, an adaptation of the methodology of engagement and social transformation: education, structure and stimulus, focusing on education the best efforts, as the essential foundation of structure and stimulation.